An improved decomposition approach toward energy rebound effects in China: Review since 1992. (July 2021) - Chen, Jiandong; Gao, Ming; Shahbaz, Muhammad; Cheng, Shulei; Song, Malin
Abstract: Although technological progress has greatly reduced energy use, the actual energy savings have always been lower than the potential conservations. This is known as the "energy rebound effect." This paper estimated energy rebound effects of China's fossil and non-fossil fuel consumption. Additionally, this study derived an improved approach for decomposition of energy rebound effects without presupposing production function forms. Results shows that the fossil fuel rebound effect was higher than the non-fossil fuel, which may be due to the heterogeneous impacts of technology on potential fossil and non-fossil energy savings. Furthermore, fossil and non-fossil energy rebound effects were both predominantly caused by the substitution effect instead of the output effect. Hence, vigorously improving non-fossil energy efficiency will help reduce the fossil energy rebound effect. Highlights: China's energy rebound effect (Re) was estimated for 1992–2013. China's energy technology mainly centered on improving fossil energy efficiency. Total Re was found to be dominated by fossil Re. Total Re was further attributed mainly to the substitution effect.